Monetary policy and the dangers of deflation: Lessons from Japan - Daniel Leigh (The Johns Hopkins University, Department of Economics, 2004)
This paper investigates how monetary policy can help to avoid the liquidity trap by studying the experience of Japan. First, I analyze how the Bank of Japan conducted interest rate policy over the 1990s as the economy entered a deflationary slump. I use a new method of estimating the policy rule with a time-varying inflation target and a time-varying natural rate of interest. The estimation strategy reveals that the Bank's implicit inflation target declined to about 1% in the 1990s from about 2.5% in the 1980s. I also find that the policy rule respects the Taylor principle and is forward looking. Such a Taylor rule does not depart from what was perceived as current best practice. It thus seems that the problem arose because of a series of adverse shocks and not because of an extraordinary monetary policy mistake. Next, I investigate whether an alternative monetary policy rule could have avoided the liquidity trap despite these shocks. I find that targeting a higher rate of inflation of 2-3% would not have provided much protection against hitting the zero bound on nominal interest rates. Similarly, a policy of responding more aggressively to the inflation gap while keeping the low inflation target would have provided little improvement in economic performance. The economy also still enters the trap under a nonlinear policy rule that commits the central bank to keeping interest rates at zero even after the economy begins to recover. However, I find that a rule that combined both (i) a higher inflation target of about 3%, and (ii) a more aggressive response to the inflation gap would have improved the economy's performance and avoided the zero bound.
Keywords: C22; E31; E52; 330; Deflation; Kalman filter; liquidity trap; Taylor rule; Geldpolitik; Liquiditätspräferenz; Deflation; Taylor-Regel; Japan; Zustandsraummodell